PENGARUH PEMBELAJARAN INKLUSIF GENDER TERHADAP PENINGKATAN HASIL BELAJAR BAHASA INDONESIA SISWA MTs MITRA PSW STAIN WATAMPONE - fatimah, sitti (PSW, 2010)
The result of the research show, firstly, the application of inclusive gender teaching have a significant effect to ward the achievement of student in bahasa Indonesia, before the application of inclusive gender teaching, the mean score of the girl student was 73.33 which had significant different with the boy student 70.05. after the application of inclusive gender teaching, the mean sore of the students was 75.24, which did not have significant different with the boy studentsâ mean score. This indicated there is a correlation between inclusive gender teaching and student achievement. Secondly, the application of inclusive gender teaching based on the result of interview with the teachers was successful. It was indicated by the motivation of student in learning bahasa Indonesia was improved. Particulary, in reading and writing competency, boy students were equal with girl students.